OPTIMASI PENEMPATAN RECLOSER UNTUK MEMPERBAIKI KEANDALAN PADA PENYULANG LEMBONGAN MENGGUNAKAN METODE PARTICLE SWARM OPTIMIZATION-FUZZY - Luis da Costa, Jaime; Sari Hartati, Rukmi; Setiawan, Widyadi (Jurnal SPEKTRUM, 2018)
In Bali, especially at Tiga Nusa, the need for electricity is increasing along with the development of the construction of resorts and hotels. In this study, a sample of cases was taken in 2014 regarding the Lembongan feeder network system which was still installed with several LBS (Load Break Switch) which used to localize interference. Therefore, to anticipate interference and improve the reliability of feeders, one of many ways is to add an automatic back cover (recloser). This study aims to determine the optimal recloser location in the Lembongan feeder by using a combined method of fuzzy logic and particle swarm optimization with the help of MATLAB software. The results of this study obtained the best location of the recloser in group 5, namely the area between LBS SD 3, LBS Celagi Empak, and LBS Lembongan by adding one recloser. The SAIFI value is 1,9471 times / customer / year and the SAIDI value is 1,4596 hours / customer / year where the world class service parameter standard for the SAIFI reliability index is 3 times / customer / year and the SAIDI reliability index is 2,5 hours / customer / year.